Assembly of Pt nanowires into cubelike superstructures supported on aligned carbon nanotubes as highly stable electrocatalysts - Wu, Renbing (2013)
Go nano! Cubelike Pt nanowire superstructures supported on vertically aligned bamboo-shaped carbon nanotubes (see the FESEM image) are used as electrocatalysts for fuel cells. They exhibit remarkably improved stability over the commercial Pt/C catalyst made of Pt nanoparticles on amorphous carbon.